2019
DOI: 10.1088/1361-6560/ab2a32
|View full text |Cite
|
Sign up to set email alerts
|

Modeling ultrasound attenuation in porous structures with mono-disperse random pore distributions using the independent scattering approximation: a 2D simulation study

Abstract: Osteoporosis is increasingly prevalent, and the societal impact of age-related bone loss is becoming progressively greater. It is estimated that 4-6 million U.S. women have osteoporosis, and that 13-17 million have osteopenia (Looker et al 1997). The gold standard for the diagnosis of osteoporosis is the measurement of bone mineral density (BMD) using dual-energy x ray absorptiometry (DXA) for trabecular/cancellous bone and high resolution peripheral quantitative computed tomography (HR-pQCT) for cortical bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…A recent study by Milazzo et al demonstrated with micro-CT and SEM images that silk scaffolds have an irregular sponge shape characterized by alveolar structures and pores of various diameters while also possessing a relatively smooth surface [39] . These pores while making it an ideal tissue engineering scaffold to grow cells, also lead to multiple scattering events [40] , generating echoes similar to ultrasound signatures of tissue. For the 5 MHz transducer, the signal amplitude throughout the 5 mm depth decreased by a ratio of approximately 1.59 which corresponds to an attenuation of 4.02 dB ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Milazzo et al demonstrated with micro-CT and SEM images that silk scaffolds have an irregular sponge shape characterized by alveolar structures and pores of various diameters while also possessing a relatively smooth surface [39] . These pores while making it an ideal tissue engineering scaffold to grow cells, also lead to multiple scattering events [40] , generating echoes similar to ultrasound signatures of tissue. For the 5 MHz transducer, the signal amplitude throughout the 5 mm depth decreased by a ratio of approximately 1.59 which corresponds to an attenuation of 4.02 dB ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This enables us to study the attenuation behavior in different scattering regimes (kϕ < 0.8: low scattering regime, 0.8 < kϕ < 1: medium scattering regime, 1 < kϕ: high scattering regime). Some scattering models such as the Independent Scattering Approximation are suited for specific scattering regimes and cannot be expected to describe the attenuation in other regimes accurately (Yousefian et al 2019). For each pore diameter-density combination, 16 different simulations are executed to investigate the whole spectroscopy range (1-8 MHz frequency range with 0.5 MHz intervals).…”
Section: Numerical Measurementsmentioning
confidence: 99%
“…Second model: Previous works done by the authors Yousefian et al (2019) showed that the Independent Scattering Approximation (ISA) can be used to accurately predict the attenuation in simplified structures of cortical bone for kϕ < 1. Briefly, the ISA predicts the scattering attenuation as follows:…”
Section: Modeling Attenuationmentioning
confidence: 99%
See 2 more Smart Citations